Expanding the green gaming horizon: a conceptual analysis of and proposed guidelines for upscaling environmental game usage in climate education - Fjællingsdal, Kristoffer Skomsøy (Frontiers in Psychology, 2025)
Despite the now unequivocal notion that climate change is driven by anthropogenic activity, communication between concerned climate scientists and laypeople about the severity of the issue is still muddy. Although creative and more approachable venues of communication to climate change and sustainability issues are being explored more regularly than before, there is still room for improvement and upscaling in the attempts to link scientists and laypeople together in the understanding of these outstanding issues. This also applies to the field of environmental gaming, which has become more popular in the recent decade. Despite this increasing popularity, however, most environmental gaming studies exist as small-scale pilot studies that often result in generating limited, albeit promising results in terms of increasing awareness and knowledge around environmental topics. This article explores the use of games in climate- and sustainability education and provides a set of assisting guidelines to ease the process of using games as communication tools about these pressing issues, as well as providing advice on how to upscale environmental gaming from a set of limited pilot studies.